Financial controls to control corruption in an African country: Insider experts within an enabling environment. (13th April 2020) - Lassou, Philippe J. C.; Hopper, Trevor; Soobaroyen, Teerooven
Abstract: This study analyses an implementation of a government accounting reform in Benin directed at redressing fraudulent and corrupt practices. Although reforms to improve public administration and to mitigate corruption in Africa often have disappointing outcomes, our case study involving systems for payment of supplier invoices, payroll matters, and debt certificates had encouraging findings. The systems reduced inefficiencies and corrupt practices. An "enabling environment" (its main elements being emancipatory space, empowered participation, and ethical leadership) encouraged the deeper involvement of committed, expert, and ethical local civil servants in establishing effective financial controls. In the context of anticorruption reforms, this illustrates that public sector organizations in Africa should not invariably be regarded as monolithic bureaucratic top‐down entities, staffed by civil servants who are either passive "bystanders, " purely self‐interested "players, " or insufficiently expert, and hence in need for more training, and of imported, expensive, accounting systems implemented by foreign consultants. In contrast, the paper argues that, within a suitable environment, granting indigenous experts enough latitude to enact incremental yet substantive accounting changes at the local level may be more effective.